Ciclovias: Possibilidades de Implantação em Goiânia. - Domingos, John Moreira (2012)
Macro phenomenon as capitalism and the industrial revolution imposed drastic changes in the lives of huge populations. Urbanization, a major consequence of these, brought problems of all kinds. Among them, those related to urban mobility are presented as a complex challenge to be solved. As the object of study, it appears that the city of Goiânia in 2011 joined the group of five Brazilian cities with more than one million vehicles, with a rate of vehicles/capita of 0.95 (DENATRAN, 2011e IBGE, 2010 ), as the fifth capital with a higher mortality rate in the total of accidents and motorcycle accidents seventh (www.samugoiania.com.br). But in 50 years, was one of Goiânia Brazilian cities that had more bikes for people (DEUS and BARREIRA, 2006), has been called the Brazilian capital of bike (OPTION JOURNAL, 1980), in 1980 there were 47.783 daily movements by bicycles and; 50,000 users, representing 23% of the economically active population of the city (IPLAN, 1981). Therefore, this dissertation presents the benefits of bicycle use and road cycle infrastructure as an important strategy in addressing conflicts of urban mobility and also seeks to highlight the call and the historical roots cycling of Goiânia.